The importance of democracy for economists - Fernández-Baca, Jorge (1991)
Economic theory has recently abandoned its attitude of indifference toward democracy and its importance for the functioning of markets. With the help of the Findlay-Wilson model, it can be shown how the absence of a democratic regime can bring stagnation and decline for society. Representative democracy can hardly be replaced by "direct democracy", as some intellectuals and politicians are presently proposing in Peru.